Climate Sensitivities of Carbon Turnover Times in Soil and Vegetation: Understanding Their Effects on Forest Carbon Sequestration. Issue 3 (24th February 2022) - Ge, Rong; He, Honglin; Zhang, Li; Ren, Xiaoli; Williams, Mathew; Yu, Guirui; Luke Smallman, T.; Zhou, Tao; Li, Pan; Xie, Zongqiang; Wang, Silong; Wang, Huimin; et al.
Abstract: The high uncertainty associated with the response of terrestrial carbon (C) cycle to climate is dominated by ecosystem C turnover time ( τ eco ). Although the relationship between τ eco and climate has been extensively studied, significant knowledge gaps remain regarding the differential climate sensitivities of turnover time in major biomass ( τ veg ) and soil ( τ soil ) pools, and their effects on vegetation and soil C sequestration under climate change are poorly understood. Here, we collected multiple time series observations on soil and vegetation C from permanent plots in 10 Chinese forests and used model‐data fusion to retrieve key C cycle process parameters that regulate τ soil and τ veg . Our analysis showed that τ veg and τ soil both decreased with increasing temperature and precipitation, and τ soil was more than twice as sensitive (1.27 years/°C, 1.70 years/100 mm) than τ veg (0.53 years/°C, 0.40 years/100 mm). The higher climate sensitivity of τ soil caused a more rapid decrease in τ soil than in τ veg with increasing temperature and precipitation, thereby significantly reducing the difference between τ soil and τ veg ( τ diff ) under warm and humid conditions. τ diff, an indicator of the balance between the soil C input and exit rate, was strongly responsible for the variation (more than 50%) in soil C sequestration. Therefore, a smaller τ diff under warm and humid conditions suggests a relatively lower contribution from soil C sequestration. This information has strong implications for understanding forest C‐climate feedback, predicting forest C sink distributions in soil and vegetation under climate change, and implementing C mitigation policies in forest plantations or soil conservation. Plain Language Summary: Carbon turnover time is the average time that a carbon atom stays in an ecosystem from entrance to exit. Together, ecosystem carbon input via photosynthesis (i.e., productivity) and carbon turnover time determine ecosystem carbon sequestration. However, in contrast to the well‐studied ecosystem productivity, carbon turnover time was found to dominate the uncertainty in terrestrial carbon sequestration and its response to climate. However, the climate sensitivities of carbon turnover times in various plant and soil pools and their effects on carbon storage have not been well‐studied. Here, we quantified that carbon turnover time in soil ( τ soil ) was more sensitive to climate than that of vegetation ( τ veg ). This finding indicated the difference between τ veg and τ soil ( τ diff ) being shortened in warm and humid regions. We further found that τ diff, as an indicator of the balance between soil carbon input and the carbon exit rate, is closely associated with the capacity for soil carbon sequestration. Therefore, a decreasing τ diff with increasing temperature/precipitation indicates a smaller proportion of carbon sequestered by soil than vegetation. Our findings facilitate understanding of carbon‐climate feedback and the prediction of carbon sink distributions under climate change and could guide the implementation of carbon mitigation policies for vegetation/soil conservation. Key Points: The carbon turnover time in soil ( τ soil ) has a higher climate sensitivity to temperature and precipitation than that of biomass ( τ veg ) The strong climate responses of woody allocation and soil decomposition in combination contribute to the higher climate sensitivity of τ soil than τ veg The higher climate sensitivity of τ soil than τ veg led to a decreased soil carbon sequestration capacity under warm and humid conditions